PENGARUH MODEL GAME BASED LEARNING BERBANTUAN ZEP QUIZ TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA KELAS XI SMAN 1 BANGSAL - Istiqomah, Oktavia; Rahayuningsih, Suesthi; Nurul Imanah, Ulil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low mathematics learning motivation is a serious problem in high school education, especially when teaching methods are monotonous and teacher-centered. This study aims to examine the effect of the Game Based Learning model using ZEP QUIZ on the mathematics learning motivation of grade XI students at SMAN 1 Bangsal. This study used a quantitative approach with a quasi-experimental design of the nonequivalent posttest only control group. The sample consisted of the experimental class (n=32) receiving the Game Based Learning model using ZEP QUIZ, and the control class (n=32) receiving conventional learning. Data were collected using a learning motivation questionnaire adapted from the Fitriana instrument (2021) comprising 12 items across 4 indicators. Data analysis employed the independent samples t-test for significance testing, a one-tailed test (right-tailed) to determine the direction of the effect, and effect size measurement using Cohen's d, Hedges' correction, and Glass's delta. The results showed that: (1) there was a significant difference in learning motivation scores between the experimental and control classes (t = 6.937; df = 62; p < 0.001); (2) the direction of the effect was positive, as evidenced by the right-tailed test (t' = 7.322 > t critical = 1.696), with the experimental class mean (x̅ = 49.22) significantly higher than the control class (x̅ = 43.75); and (3) the effect size was classified as very large (Cohen's d = 1.734; Hedges' correction = 1.713; Glass's delta = 1.510), all exceeding the threshold of 0.8. These findings indicate that the Game Based Learning model using ZEP QUIZ is effective in positively and significantly improving the mathematics learning motivation of high school students.